Optimizing Patient Outcomes Through Multidisciplinary Cooperation in Medical Departments: A Comprehensive Review - Alnahhas, Alhanouf Mohammed; Assiri, Amnah Ibrahem Mohammad; Al-Qahtani, Saeed Ali Mohammed; Alfarhan, Huda Abdulrahman Besher; Alshahrani, Salihah Ahmed Awadh; Asiri, Talah Abdullah ali; asiri, Maherah Ibraheem Mohammed; Alshehri, Ali Mohammad Abdulrahman (Journal of Posthumanism, 2024)
Effective healthcare delivery depends increasingly on multidisciplinary cooperation across medical departments. This review explores how interdepartmental collaboration enhances patient outcomes, clinical efficiency, and overall healthcare quality. Drawing on recent studies (2016–2025), it highlights mechanisms that enable successful cooperation—such as shared decision-making, coordinated care pathways, and interdisciplinary communication. The review identifies structural, cultural, and technological enablers of integration, including leadership support, electronic health records, and team-based performance metrics. Evidence demonstrates that cooperative models reduce medical errors, improve continuity of care, and elevate patient satisfaction. Challenges such as departmental silos, professional hierarchies, and communication barriers are also discussed, with strategic solutions proposed to overcome them. Ultimately, the study underscores the critical importance of a unified healthcare ecosystem where collaboration drives safety, innovation, and excellence in patient care.